1984
DOI: 10.1007/bf01250009
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines and serotonin in the rat central nervous system after 6-OHDA, 5-7-DHT and p-CPA

Abstract: The norepinephrine (NE), epinephrine (EPI), dopamine (DA) and serotonin (5-HT) contents were measured radioenzymatically in seven anatomically defined regions (frontal cerebral cortex, hippocampus, hypothalamus, midbrain, pons-medulla oblongata, cerebellum and spinal cord) in adult normal animals, after treatment with the tryptophan hydroxylase inhibitor p-chlorophenylalanine (p-CPA), and after the intraventricular administration of either 6-hydroxydopamine (6-OHDA) or 5,7-dihydroxytryptamine (5,7-DHT). The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 61 publications
2
29
2
Order By: Relevance
“…Biochemical and functional interac tions between the noradrenergic locus ceruleus and serotonergic raphe systems are well documented (e.g., Kostowski et aI., 1974;Saavedra et aI., 1976;Pujol, 1979;Pujol et aI., 198 1;Agren et aI., 1986;Brassard et aI., 1987) and both systems are affected by brain injury (Pappius andDadoun, 1986, 1987). PCPA has been reported to affect NE levels in brain under some conditions (Miller et aI., 1970;Rebec et aI., 1981;Reader and Gauthier, 1984;Reader et aI., 1986;Vanderwolf and Baker, 1986); in all cases, however, following higher doses than used in the present experiments. The decrease in cortical NE resulting from traumatization was statistically sig nificant when pooled groups were compared with pooled controls.…”
Section: Discussioncontrasting
confidence: 51%
“…Biochemical and functional interac tions between the noradrenergic locus ceruleus and serotonergic raphe systems are well documented (e.g., Kostowski et aI., 1974;Saavedra et aI., 1976;Pujol, 1979;Pujol et aI., 198 1;Agren et aI., 1986;Brassard et aI., 1987) and both systems are affected by brain injury (Pappius andDadoun, 1986, 1987). PCPA has been reported to affect NE levels in brain under some conditions (Miller et aI., 1970;Rebec et aI., 1981;Reader and Gauthier, 1984;Reader et aI., 1986;Vanderwolf and Baker, 1986); in all cases, however, following higher doses than used in the present experiments. The decrease in cortical NE resulting from traumatization was statistically sig nificant when pooled groups were compared with pooled controls.…”
Section: Discussioncontrasting
confidence: 51%
“…It has been shown that DHT injected into the brain region that is rich in dopaminergic terminals could change dopamine levels as well as serotonin at the injected region (Ludwig and Schwarting, 2007). However, intracerebroventricular injection of DHT as in the present study has been reported to generally spare dopaminergic neurons (Fischette et al, 1987;Reader and Gauthier, 1984;Winstanley et al, 2003). Therefore, the result of our DHT experiment suggests that the integrity of the serotonergic system is essential for the effect of fluoxetine on the dopaminergic modulation.…”
Section: Discussionmentioning
confidence: 34%
“…The reasons for these contradictory results are not clear, but there are several possible explanations. Whereas PCPA is very effective in depleting central 5-HT, it can also deplete peripheral 5-HT (Koe and Weissman, 1966) and other monoamines (Reader and Gauthier, 1984;Dailly et al, 2006), and does not affect neuropeptides colocalized in 5-HT neurons, such as thyrotropin-releasing hormone and substance P (Walker et al, 1990;Przegalinski et al, 1992). Possibly for these reasons, data obtained using PCPA have contributed previously to erroneous conclusions about the role of 5-HT in sleep (Jouvet, 1999).…”
Section: Role Of Central 5-ht Neurons In Respiratory Controlmentioning
confidence: 91%